Improvement of the adhesion properties between copper and a polyimide film - Lee, Wook-Jae; Kim, Yoon-Bae; Jee, Kwang-Ku; Lee, Woo-Young (KOREAN PHYSICAL SOC, 2008)
In this study, we investigated the adhesion properties of a NiCr(100 angstrom)/Cu(2000 angstrom) metal film on a PI film modified by Ar+O-2 Reactive ion etching (RIE) with various ion doses at an ion beam energy of 250 eV. The result for the contact angles of water indicates that the surface modification by Ar+O-2 RIE considerably decreases the contact angle from 68 degrees to 2 degrees at an ion dose of 1 x 10(18) ions/cm(2), which results in an increase by a factor of two in the surface energy. The XPS spectrum showed that C-O and C=O bonding, identified as functional groups on the modified PI surface, was increased by interaction between scissored unstable chains and reactive ions. As a result, the PI surfaces modified by Ar+O-2 RIE showed significant improvement in adhesion to overcoated metal films.
Keywords: SURFACE; ENERGY; IRRADIATION; PLASMA